Tocilizumab and COVID-19: Timing of Administration and Efficacy - Abidi, Emna; El Nekidy, Wasim S.; Alefishat, Eman; Rahman, Nadeem; Petroianu, Georg A.; El-Lababidi, Rania; Mallat, Jihad (Frontiers in Pharmacology, 2022)
Abstract Elevated concentrations of interleukin-6 have been demonstrated to be an important key factor in COVID-19 host immune impairment. It represents an important prognostic factor of harm associated with COVID-19 infection by stimulating a vigorous proinflammatory response, leading to the so-called “cytokine storm”. Therefore, immunomodulatory interventions targeting interleukin-6 receptor antagonism have been investigated as potential treatments to counterbalance the host immune dysregulation and to support the advantageous effects of corticosteroids. Tocilizumab is a recombinant humanized monoclonal antibody that has gained much interest during the COVID-19 pandemic as an interleukin-6 receptor antagonist. Various early observational studies have reported beneficial effects of tocilizumab. Moreover, consequent randomized controlled trials have subsequently shown significant positive results about tocilizumab efficacy and safety, focusing on outcomes like mortality, risk of intensive care unit admission, and the need for mechanical ventilation, while others presented conflicting findings. In this review, we first described the pathophysiology of COVID-19 infection while highlighting the role of interleukin-6. Furthermore, we also discussed the non-conclusive evidence about tocilizumab to be used as the standard of care therapy for all patients with COVID-19 pneumonia, as well as its beneficial effects in selected patients. Keywords: COVID-19 infection, SARS-CoV-2 infection, cytokine storm, interleukine-6 receptor antagonist, tocilizumab, invasive mechanical ventilation, acute respiratory distress syndrome, intensive care unit.